Youth work today: A profile - Omelczuk, Suzanna (1991)
The youth affairs field has undergone a significant transition, in terms of the types of issues central to the field and the characteristics of people working in the field, in recent years. The purpose of this study is to identify the attributes of youth workers currently engaged in the field, the activities undertaken by those workers, and the social backgrounds of young people with whom they work. More than one hundred youth workers throughout Western Australia participated in the survey. The results of the investigation describe the educational background and occupational experience of youth workers, and the characteristics of the young people with whom they work in terms of age, gender, socio-economic and occupational status, and ethnic background